From Mimbar to Smartphone: Da'wah's Evolution for Generation Z in the Digital Era - Widyawati, Tutut Indah; Syamsul Azam Noor, Bagus Muhammad; Satriyo, Bagus (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This article examines the evolution of Da’wah practices among Generation Z in the digital era, with a focus on how social media platforms shape religious engagement and outreach. Traditional Da’wah, previously conducted in physical spaces like mosques and public gatherings, has increasingly moved to digital spaces such as TikTok and Instagram, making religious teachings more accessible and appealing to younger audiences. Utilizing a qualitative literature review approach, this study synthesizes recent research to analyze the challenges and opportunities presented by digital Da’wah. The findings suggest that digital Da’wah significantly enhances youth engagement, broadens reach, and fosters community building, especially through content that is humanistic, creative, and contextually relevant. However, the study also reveals challenges, such as the potential for misinformation and oversimplification of religious content in these new media. This article contributes to scholarly discourse by offering insights into the strategic use of digital platforms for Da’wah, highlighting how religious leaders can effectively engage Generation Z while promoting a nuanced and comprehensive understanding of Islamic teachings in a digital context. These findings underscore the need for responsible content curation and digital literacy to maintain the integrity of religious messages and address the unique needs of Generation Z.